Cultural variation in age perceptions and developmental transitions - Vargas, Michelle E.; Carrillo, Alejandro; Giasson, Hannah L.; Chopik, William J. (Frontiers in Social Psychology, 2024)
As people age, people increasingly report feeling younger than their actual age and "push off" when they think older adulthood starts, presumably to create and maintain psychological distance from the stigma of being an older adult. However, to date, such age perceptions and attitudes have mostly been studied in Western cultures (e.g., the United States and Europe). However, cultures vary in their perception of older adulthood and aging, suggesting that the extent to which people engage in these distancing processes might differ across cultures. In the current study, we examined age differences in age perceptions and perceived developmental transitions (e.g., when does someone move from middle age to older adulthood?) in 13 different countries with over one million people total. We found that age-group distancing was present in each country but that this pattern was less pronounced in South Korea. Results are discussed in the context of crosscultural variation in aging attitudes and the mechanisms that give rise to variation in age perceptions.